Synergistic Effects of Honey and Herbal Bioactives in Cancer Suppression - Aprilia, Waheni Rizki; Hidayah, Nurul; Ari, Psn Masruri Sulistiyanto (International Journal of Cell and Biomedical Science, 2025)
Natural bioactives from medicinal plants and honey possess remarkable antioxidant and anticancer properties. However, limited studies have evaluated their synergistic efficacy as combination formulations. This study aimed to develop and characterize a honey–herbal formulation with potential anticancer activity against human breast cancer cells (MDAMB) while ensuring minimal cytotoxicity toward non-cancerous mesenchymal stem cells (MSCs). The formulation was prepared by blending ethanolic herbal extract with pure natural honey in optimized ratios. Organoleptic characteristics were assessed by sensory evaluation. Antioxidant capacity was determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Organoleptic analysis showed acceptable color, aroma, texture, and pH profiles. The honey exhibited strong antioxidant (IC₅₀ = 60 ± 0.7 ppm) compared with external honey and others sample. The formulation demonstrates potential as a functional nutraceutical or adjunctive natural therapy for breast cancer management, warranting further in vivo and molecular pathway investigations.